Serum levels of TGF-β1 in patients of diabetic peripheral neuropathy and its correlation with nerve conduction velocity in type 2 diabetes mellitus. Issue 1 (January 2016) - Hussain, Gauhar; Rizvi, S. Aijaz Abbas; Singhal, Sangeeta; Zubair, Mohammad; Ahmad, Jamal
Abstarct: Aims: To correlate serum levels of TGF-β1 with motor and sensory nerve conduction velocities in patients of type 2 diabetes mellitus Materials and methods: The study was conducted in diagnosed type 2 diabetes mellitus patients which were divided in patients with clinically detectable peripheral neuropathy of shorter duration ( n  = 37) and longer duration ( n  = 27). They were compared with patients without clinical neuropathy ( n  = 22). Clinical diagnosis was based on neuropathy symptom score (NSS) and Neuropathy disability score (NDS) for signs. Blood samples were collected for baseline investigations and estimation of serum TGF-β1. Nerve conduction velocity was measured in both upper and lower limbs. Median, Ulnar, Common Peroneal and Posterior Tibial nerves were selected for motor nerve conduction study and Median and Sural nerves were selected for sensory nerve conduction study Results: In patients of type 2 diabetes mellitus with clinically detectable and serum TGF-β1 showed positive correlation with nerve conduction velocities Conclusion: High level of TGF-β1 in serum of T2DM patients with neuropathy show possible contribution in development of neuropathy. Due to its independent association this cytokine might be used as biomarker for diabetic peripheral neuropathy